2017
DOI: 10.1093/europace/eux351
|View full text |Cite
|
Sign up to set email alerts
|

Different responses to exercise between Andersen–Tawil syndrome and catecholaminergic polymorphic ventricular tachycardia

Abstract: In patients with ATS, VAs with RBBB morphology were frequently observed at baseline and suppressed at peak exercise. In contrast, exercise provoked VAs with mainly LBBB morphology in patients with CPVT. In adjunct to clinical and baseline ECG assessments, exercise testing might be useful for making the diagnosis of ATS vs. CPVT, both characterized by bidirectional VT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Noticeably, the ECG during exercise testing is also different for both groups: ventricular arrhythmias appear early, stop at the peak of exercise to finally reappear after the end of exercise for KCNJ2 -mutated patients with CPVT, while in other CPVT patients they appear early, increase to reach the maximum at peak and stop at rest. The morphology of PVC is different between the two groups: right BBB pattern is more frequent in KCNJ2 -mutated patients with CPVT whereas left BBB pattern if more associated with mutations in other genes ( Inoue et al, 2018 ). Interestingly, proband 2 of our study presented a Pierre Robin sequence.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Noticeably, the ECG during exercise testing is also different for both groups: ventricular arrhythmias appear early, stop at the peak of exercise to finally reappear after the end of exercise for KCNJ2 -mutated patients with CPVT, while in other CPVT patients they appear early, increase to reach the maximum at peak and stop at rest. The morphology of PVC is different between the two groups: right BBB pattern is more frequent in KCNJ2 -mutated patients with CPVT whereas left BBB pattern if more associated with mutations in other genes ( Inoue et al, 2018 ). Interestingly, proband 2 of our study presented a Pierre Robin sequence.…”
Section: Discussionmentioning
confidence: 98%
“…KCNJ2 -mutated patients with CPVT are all females ( Andelfinger et al, 2002 ; Tester et al, 2006 ; Kukla et al, 2014 ), for whom the age of onset or diagnosis ranges from 2 to 36, with a mean around 15, as compared to 8 years old for RYR2 -related CPVT ( Ackerman et al, 2011 ). In addition, VA reported in patients with KCNJ2 mutations have been described as milder than in RYR2 mutated patient, especially rarely leading to syncope or sudden cardiac arrest ( Andelfinger et al, 2002 ; Tristani-Firouzi et al, 2002 ; Delannoy et al, 2013 ; Kukla et al, 2014 ; Inoue et al, 2018 ). Reported KCNJ2 -mutated patients with CPVT consistently show an abnormal resting ECG, while only exercise stress test triggers detectable ECG signs for other CPVT patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case-control study of 26 ATS patients, Inoue et al found increased ventricular arrhythmias with increasing heart rate in 35% of cases. The arrhythmias C o r r e c t e d P r o o f disappeared as the heart rate approached its maximum but increased again in the recovery phase [28].…”
Section: Anderson-tawil Syndromementioning
confidence: 97%
“…Due to the recent discovery of TRDN 47 , CALM1 44 , and TECRL 55 genes as causes of CPVT, their inclusion in previous guidelines had not been contemplated, but we recommend screening after exclusion of RYR2 and CASQ as causes of this disease. Other genes to consider in a genetic test are KCNJ2 [71][72][73][74] and ANKB 75 .…”
Section: Genetic Testingmentioning
confidence: 99%